Объектінің жоғалуы: Хайдеггердің ядролық фантазмының жүзеге асуы және заттар интернеті - Turarbekova, L. V. (ҚазҰУ хабаршысы. Философия, саясаттану және Мәдениеттану, 2022)
The increasing role of digital technologies in the modern world causes an ambiguous reaction of the humanitarian community and related fields of knowledge. On the one hand, it is indisputable that in the future the partial or complete digitalization and virtualization of most spheres of everyday human activity (labor, economic, cultural, social, interpersonal relations, etc.) will increase. On the other hand, the speed with which digital technologies are developing causes a different range of moods – from admiration to panic – and makes us think about the consequences for humanity of such a rapid technological development, capable of subjugating any, even the most intimate aspects of modern human life. Modern times know at least two tragic episodes, two world wars, the consequences of which made the thinkers of the XX century doubt the adequacy of the idea of scientific and technological progress in its application to ideas about the good for man. At the same time, there are two well-defined outlines of the main solutions to this problem. The first is the technophobic ideal of abandoning further scientific and technological development, a call for a return to a minimally cultivated state of man in the name of preserving "man" as a humanitarian ideal. The second is an attempt to consider possible new ways to understand "man", "human" with the prospect of developing new ethical principles in view of the recognition of the inevitability of technological development as part of culture, inevitably and purely human world. The article is devoted to the analysis of the idea of the disappearance of the object and the change of the subject-object vector of attention in the works of Martin Heidegger ("Being and Time", "Question of Technology", "Thing") in the context of the development of modern digital technologies and the new existential attitudes arising in this process. Keywords: digital technologies, digitalization, technology, culture, subject and object, person, humanity, digital philosophy, being